The Effect of Combined Observational and Shadow Practices on Learning Dart Throw Skill - Narges Abdoli; Nasrin Parsaei; Hassan Rohbanfard (University of Tehran, 2018)
The aim of the present study was to examine the effect of combined observational and shadow practices on learning dart throwing skill. 60 female high school students (17-19 years old) who volunteered to participate in this study were selected and randomly assigned to 5 groups after pretest: observational, shadow, physical, combined (observational-shadow) and the control. During the acquisition phase, the practice groups practiced 60 trials of dart throwing skill based on the specific instructions for each group. 10 minutes after the acquisition phase, immediate retention/transfer tests were conducted and after 24 hours of detraining, delayed transfer/ retention tests were carried out. ANOVA with repeated measures (P=0.05) revealed that practice groups had significantly better performances than the control group (P>0.05). Also, physical and combined groups had significantly better performances than the observational and shadow groups (P<0.05). The combined group enjoyed learning equal to physical practice (P<0.05). Overall, the results indicated that combined observation and shadow practices resulted in learning equal to physical practice. These findings suggest that as this practice method can be applied anytime and anywhere with minimum requirements, it can reduce the educational time and costs and even it can be replaced by physical practice under specific circumstances.